К определению модуля, углов наклона и чисел зубьев в передачах Новикова некруглыми колесами - Утутов, Н. Л.; Карпов, А. П.; Баюн, В. Н. (НТУ "ХПИ", 2009)
Описано порядок розрахунку некруглих зубчастих коліс у загальному вигляді; представлено залежності для визначення радіусів кривизн, координат центрів кривизн центроїд, довжин центроїд залежно від функції передатного відношення.

The procedure of design of noncircular toothed gear wheel in a general view is described; dependences for determination of radiuses of curvature, coordinates of the centers of centrode curvature, centrode lengths are submitted depending on function of transmission ratio.
Keywords: зацепление Новикова; параметры передачи; передаточное отношение; радиусы центроид; эвольвентное зацепление